Stroke outcomes in Thai elderly patients treated with and without intravenous thrombolysis - Pornpatr A. Dharmasaroja; Sombat Muengtaweepongsa; Junya Pattaraarchachai; Permphan Dharmasaroja (Neurology International, 2013)
Higher mortality was found in very old patients with acute ischemic stroke treated with intravenous recombinant tissue-plasminogen activator (rtPA) as compared to younger patients. The benefit of thrombolytic treatment in this particular subgroup is still a subject of debate. The purpose of this study was to compare stroke outcomes in Thai patients aged over 70 years treated with and without intravenous rtPA. This was a retrospective review of sequential cases and was not a randomized controlled study. One-hundred and five patients with acute ischemic stroke aged over 70 years who were treated with intravenous rtPA and 105 patients without rtPA treatment (control group) were included in the study. Patients’ base-line characteristics and study outcomes of interest were compared. There were significant differences in the base-line characteristics of the two groups. However, for the subgroup of patients aged over 80 years, these characteristics were similar. Those who were treated with intravenous rtPA had a higher rate of favorable outcomes (40% vs 16%; P=0.137) and a lower rate of mortality (22% vs 44%; P=0.128) than patients who did not receive rtPA treatment. In well-matched subgroups of patients aged over 80 years, our retrospective review revealed there was a trend of a higher rate of favorable outcome and lower mortality in patients receiving rtPA treatment. More study is needed to further confirm the suggested benefit of thrombolysis in Asian octogenarian acute stroke patients.